2020
DOI: 10.4103/jehp.jehp_237_19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of case-based teaching and flipped classroom methods in comparison with lecture method on learning and satisfaction of internship students in surgery

Abstract: INTRODUCTION: Teaching is one of the most important needs of human societies, and selecting the best method of teaching is so important to improve the teaching as well as learning of students. The purpose of this study was to determine the effect of case-based teaching (CBT) and flipped classroom methods in comparison with lecture method on students’ learning and satisfaction at internship of Department of General Surgery, Isfahan University of Medical Sciences. MATERIALS AND METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The total satisfaction of students with the teaching form, teaching content, and class hours, classroom atmosphere, academic burden, evaluation system, and learning guidance method, autonomous learning ability, learning enthusiasm, and participation in interaction adopted by the Introduction to Environmental Health Science exceeded 85%, which was consistent with Kolahdouzan et al’s ( 16 ) teaching reform of surgery through the use of the case-based learning of the flipped classroom, and the improvement of students’ learning satisfaction. There were many teaching contents in Introduction to Environmental Health Science.…”
Section: Discussionsupporting
confidence: 87%
“…The total satisfaction of students with the teaching form, teaching content, and class hours, classroom atmosphere, academic burden, evaluation system, and learning guidance method, autonomous learning ability, learning enthusiasm, and participation in interaction adopted by the Introduction to Environmental Health Science exceeded 85%, which was consistent with Kolahdouzan et al’s ( 16 ) teaching reform of surgery through the use of the case-based learning of the flipped classroom, and the improvement of students’ learning satisfaction. There were many teaching contents in Introduction to Environmental Health Science.…”
Section: Discussionsupporting
confidence: 87%
“…[ 14 ] Not only participation of students increased group dynamics and sharing among students but also active participation of students motivated the faculties or the facilitators to deliver more relevant information in a more effective way; however, some other teachers had an opinion that in this process, most of the contents ought to be delivered are missed due to time constraints and format limitation. [ 15 ] Orban et al . stated that with the implementation of CBL in regular curriculum, the student's knowledge transformed from theory-based bookish knowledge to analytical reasoning type which would be helpful for their clinical practice or professional life.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to some studies about the application of integration programs on student learning. [ 8 11 20 21 22 23 ] Bahari et al . [ 8 ] showed that the level of learning in students improved by the integration of educational programs in physiopathology courses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Kolahdouzan et al . [ 23 ] determined the effect of the case-based teaching method in comparison with the lecture method on students’ learning and satisfaction at the internship of Department of General Surgery, Isfahan University of Medical Sciences and the students’ satisfaction with case-based learning method was higher than that of lecture method. Dulloo et al .…”
Section: Discussionmentioning
confidence: 99%